Advances of berberine against metabolic syndrome-associated kidney disease: Regarding effect and mechanism - Liu, Ya-Fei; Wang, Huan-Huan; Geng, Yin-Hong; Han, Liang; Tu, Sheng-Hao; Wang, Hui (Frontiers in Pharmacology, 2023)
The prevalence of Metabolic syndrome (MetS) is drastically growing worldwide, subsequently resulting in MetS-associated kidney disease. According to western theories, preventing blood pressure, lipid, glycose, obesity and improving insulin resistance, couple of medications are required for MetS. It not only lowers patients’ compliance but also elevates adverse reactions. Taking this into account, we attempt to seek answer from complementary and alternative medicine. Ultimately, berberine (BBR) was picked out due to its efficacy and safety on MetS through multi-pathways and multi-targets. The effects and mechanisms of BBR on obesity, insulin resistance, diabetic nephropathy, hypertension, hyperlipidemia, and hyperuricemia were elaborated. In addition, the overall properties of BBR and interventions on various kidney diseases were also collected. However, more clinical trials are expected to further identify the beneficial effects of BBR.